Analyses of the Design of Multirows Vaneless Staggered Counter-Rotating Turbine - Zhongye Wu; Yukun Zhang; Qingfen Ma; Jingru Li (International Journal of Aerospace Engineering)
Compared with a conventional turbine, counter rotating turbine has larger thrust weight ratio, shorter axial distance, and higher efficiency. It has been widely used in high-performance aviation. In conventional counter-rotating turbine, HPT is located in the front of LPT, and only a stator row can be eliminated. The layout limits the turbine weight and efficiency. Therefore, the staggered counter rotating turbine is proposed, and the staggered counter rotating turbine can eliminate the all-internal stators, which can greatly improve the turbine weight and efficiency. The staggered counter rotating turbine is the development and improvement of counter rotating turbine. Due to the elimination of the all-internal stators, the downstream rotor will suffer from the insufficient inlet swirl, which is the main question in staggered counter rotating turbine design. Furthermore, the turbine outlet angle is also an important parameter to evaluate the turbine design. The coordination of inlet swirl and outlet Mach number and the outlet angle is discussed by the theoretical method. In order to verify the design method, two-dimensional throughflow design, blade design, and three-dimensional numerical analysis are performed. Expansion ratios and efficiency at the speed combinations of the 80% to 105% are discussed to reveal the turbine characteristics at off-design conditions. An adiabatic total-to-total efficiency of 92.1% with expansion ratio of 4.47 at design point is obtained and achieves the initial design goal very well. The paper is aimed at providing a technical approach to improve the thrust weight ratio, efficiency of high bypass turbofan engines, and provide new ideas for the development of aeroengines.